2022
DOI: 10.3389/fvets.2022.1064017
|View full text |Cite
|
Sign up to set email alerts
|

Black soldier fly larvae used for environmental enrichment purposes: Can they affect the growth, slaughter performance, and blood chemistry of medium-growing chickens?

Abstract: IntroductionThis research has been aimed at evaluating the effects of live black soldier fly larvae (BSFL) (Hermetia illucens) on the growth, slaughtering performance, and blood parameters of medium-growing chickens.MethodsA total of 240, 28-day-old, Label Rouge Naked Neck chickens were allotted to four experimental groups, according to the gender (males-females) and to the absence (control group, C) or presence (larvae group, L) of a dietary supplementation with 10% live BSFL, on the basis of the expected ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(89 reference statements)
2
8
0
Order By: Relevance
“…Partially in agreement with the present trial, Bellezza Oddon et al [ 18 ] observed a similar overall FCR between broilers fed live BSF larvae and control birds, while they recorded a significant reduction in the overall FCR detected in broiler chickens fed live YM larvae [ 18 ]. The results of the present trial are also in line with the results reported by Bongiorno et al [ 17 ] for Label Necked Neck chickens fed BSF live larvae provided at 10% of the expected ADFI, where, despite a higher amount of larvae provided compared with the present study, LW, ADG, ADFI and FCR were unaffected. By contrast, the daily provision of live BSF larvae (10% of the expected ADFI) to turkeys led to higher ADFI and body weight gain and a lower FCR than the control group [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Partially in agreement with the present trial, Bellezza Oddon et al [ 18 ] observed a similar overall FCR between broilers fed live BSF larvae and control birds, while they recorded a significant reduction in the overall FCR detected in broiler chickens fed live YM larvae [ 18 ]. The results of the present trial are also in line with the results reported by Bongiorno et al [ 17 ] for Label Necked Neck chickens fed BSF live larvae provided at 10% of the expected ADFI, where, despite a higher amount of larvae provided compared with the present study, LW, ADG, ADFI and FCR were unaffected. By contrast, the daily provision of live BSF larvae (10% of the expected ADFI) to turkeys led to higher ADFI and body weight gain and a lower FCR than the control group [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…The gross energy (GE) content of the larvae was determined using an adiabatic calorimetric bomb (C7000; IKA, Staufen, Germany). Finally, the amino acid analysis was performed as reported by Bongiorno et al [ 17 ]. The proximate composition of the BSF and YM larvae of both early and late instars is reported in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations